Variation of Aedes aegypti Larvae Predation by Toxorhynchites violaceus Larvae (Diptera: Culicidae) According to Habitats Dimensions - Albeny, Daniel Simões; Rosa, Cassiano Sousa; Krüger, Rodrigo Ferreira; Ataíde, Lívia Maria Silva; Vilela, Evaldo Ferreira (BioAssay, 2012)
Non-biodegradable containers that accumulate water are commonly found in urban environment, and make ease the larval development of Aedes aegypti mosquito. Wich can make chemical control very difficult and less effective. Biological control is an alternative method, and the predators Non-biodegradable containers that accumulate water are commonly found in urbanenvironment, and make ease the larval development of Aedes aegypti mosquito, which can makechemical control very difficult and less effective. Biological control is an alternative method, and thepredators larvae of the genre Toxorhynchites (Diptera: Culicidae) are a model widely used. In this articlewe check the effect of habitat heterogeneity on Ae. aegypti larvae predation by larvae of Toxorhynchitesviolaceus. The predation model defines that the habitat heterogeneity has a significant effect on predationlevel. Larvae suffers a higher predation in containers with 1.8 centimeters in high of the water columnthan in containers with 4 and 13.4 centimeters high. In large containers, the predation of Ae. aegyptilarvae by Tx. violaceus larvae may not be efficient. However, in containers that accumulate small watervolume, as in the majority of the non-biodegradable containers, the model may be efficient.KEYWORDS – Toxorhynchites, containers, heterogeneity, Ae aegypti.